Inventory of Reptile Species in the Anai Valley Nature Reserve Area, Tanah Datar Regency, West Sumatra - Fadhil Fadhil Raid; Fitra Arya Dwi Nugraha (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
The Anai Valley Nature Reserve area is a highland area that is included in a conservation area, located between settlements and ecotourism which is vulnerable to damage to reptile species habitat due to the conversion of forest functions by the community. This study aims to determine the types of reptiles that can be found in the Anai Valley CA area, Tanah Datar Regency, West Sumatra. The method used is the Visual Encounter Survey (VES) by determining survey points in the Anai Valley CA area for data collection. The data obtained is entered into the Reptile type table by making the conservation status of the Reptile species found. The results showed that 9 species consisting of the family Scincidae were Eutropis rudis, the family Agamidae was Aphaniotis acutirostris, the Geckonidae family was Cyrtodactylus quadrivirgatus, the Elapidae family was Ophiophagus hannah, the Colubridae family was Dryocalamus subannulatus, the family Viperidae was Tropidolaemus wagleri, family Pareidae is Aplopeltura boa, family Testudinidae is Manouria emys, family Trionychidae is Amyda cartilaginea. of the number of species found in this study represented 4.01% of the number of species in Sumatra with a total and 224 species of reptiles.